Kinetic Study of Biosorption of Methyl Orange from Aqueous Solution by Tail of Black Cherry as an Eco-friendly Biosorbent - Momenheravi, Mohammad (Asian Journal of Chemistry, 2011)
The preparation of activated carbon from tail of black cherry with diluted H3PO4 of chemical activated for removal a reactive dye methyl orange from aqueous solution were reported in present study. The effect of different experimental parameters, such as initial dye concentration, adsorbent dosage, agitation speed, contact time and temperature with pH controlled were investigated. The adsorption isotherms have been analyzed by the Langmuir, Freundlich and Linear models that the Langmuir isotherm has the highest correlation coefficients. Adsorption kinetics study of methyl orange onto tail of black cherry were carried out under dyeing conditions of pH controlled and an initial concentration 50 mg/L. Pseudo first-order and second-order kinetics models were used to determine the adsorption kinetics data. The data showed that the secondorder model was the more appropriate with an activation energy 79.2 kJ/mol. Thermodynamic parameters were also evaluated. The values of enthalpy and entropy were -165 (kJ/mol) and -554.8 to -412.79 (J/mol.K) respectively, indicating that the process was spontaneous and exothermic. The results indicate that the highest percentage removal of methyl orange (97 %) can be achieved at 0.1 g of biosorbent, 10 mg/L concentration of methyl orange, contact time 18 h, agitation speed 400 rpm and temperature 25 ºC.